Uso de micro e nanotecnologia com Trichoderma - Fraceto, Leonardo Fernandes [UNESP]; Maruyama, Cintia Rodrigues; Guilger-Casagrande, Mariana; Bilesky-José, Natalia; Lima, Renata de (Embrapa, 2019)
Sem Resumo
Keywords: sem palavras-chave